El uso de plaguicidas sintéticos en la producción de hortalizas, y su incidencia en la salud de los agricultores del sector Zalapa, de la ciudad de Loja, en el período 2012 – 2013. Lineamientos propositivos - Gonzalez Mendoza; Guaman Matailo, Esperanza; Maria (2013)
The present research work the need arises due characterize pesticides used to control pests in vegetable production and its impact on the health of farmers Zalapa sector of the city of Loja, in order to determine the appropriate conditions in which to develop such production while preventing the negative effects that can cause short, medium or long term farmers. In this context, the problem is: HOW DO AFFECT THE USE OF PESTICIDES SINTETIC IN VEGETABLE PRODUCTION IN THE HEALTH SECTOR FARMERS Zalapa, Loja CITY IN THE PERIOD 2012 - 2013?, The same that arose because of the great need to reduce the risks posed by pesticides used to control pests in vegetables and thus maintain healthy social and natural environment of this sector of the farmer and the consumer. This research consists of several steps that start from the bibliography, direct observation sector, implementation of farmer interviews and surveys of residents, which allowed them to collect accurate site information investigated and the results made available to the industry, keeping and pesticide-free nature. In addition, this work was carried out using a methodology consistent with the objectives and compliance applied different methods (Scientist, inductive, deductive, statistical and descriptive) techniques (Bibliographical, interview and survey) and instruments necessary to gather information and verify hypotheses. In this way it is determined that pesticides used by farmers Zalapa sector are insecticides and herbicides among them are; Monitor 600, Bala 55, Avalanche, Furadán, Malathion, Palmarol, Lorsban and Ranger, those who have caused infections skin, abdominal pain, dizziness, headache, loss of appetite, etc. all this due to the lack of adequate protection, when applying insecticides and herbicides . Finally we consider the alternative approach to implementation which will provide opportunities to improve the health, trade, product quality while generating higher incomes useful for daily living, informing farmers that produce pesticides can be naturally, cheap and effective.